2005
DOI: 10.4321/s1139-13752005000400003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescente renal crónico: alteraciones físicas, sociales y emocionales pos-trasplante

Abstract: RESUMENLa experiencia del trasplante renal en la adolescencia produce una sensación de incertidumbre del pronóstico, pero también de esperanza y de fe de encontrar estímulos para vencer los obstáculos. Realizado en el ambulatorio de trasplante renal de un hospital público es un estudio cualitativo, descriptivo cuyo objetivo es conocer las alteraciones físicas, sociales y emocionales en la vida del adolescente pos-trasplante renal. Doce adolescentes contestaron a las preguntas de una entrevista estructurada. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In one study, 73% of recipients were at least to some extent willing to discuss their medical condition among peers . Although one study concluded that health status seldom or never interfered with social life , others reported some social life restrictions, for instance withdrawal from peers or having to leave parties earlier .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study, 73% of recipients were at least to some extent willing to discuss their medical condition among peers . Although one study concluded that health status seldom or never interfered with social life , others reported some social life restrictions, for instance withdrawal from peers or having to leave parties earlier .…”
Section: Resultsmentioning
confidence: 99%
“…Most recipients were satisfied with life (58–66%) , experienced no emotional restrictions (67%) , and did not characterize themselves as being ill (47–67%) . In one study, recipients experienced increased self‐esteem and a renewed ability to cope with physical, emotional and social stress . However, unfavorable impacts were also reported, including feelings of shame and a fragile body image , worries about the future (87%), and feelings of ‘being different’ (53%) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations